Not All Pediatric Bladder Masses are Rhabdomyosarcoma: Report of a Rare Case With Review of the Literature. Issue 8 (November 2019) - Mitra, Suvradeep; Joshi, Rashmi; Gupta, Kirti; Mahajan, Jai Kumar
Abstract : Leiomyoma of the urinary bladder in the pediatric age group is one of the rarest tumors with only 2 case reports in the English literature. Rhabdomyosarcoma is the commonest tumor at this site in this age group. It needs to be distinguished from rhabdomyosarcoma by histomorphology for appropriate treatment and management. We report the third case of urinary bladder leiomyoma arising in a 6-year-old boy with a short review of the literature.